DROSHA Knockout Leads to Enhancement of Viral Titers for Vectors Encoding miRNA-Adapted shRNAs - Hee Ho Park; Robinson Triboulet; Martin Bentler; Swaroopa Guda; Peng Du; Haiming Xu; Richard I. Gregory; Christian Brendel; David A. Williams (Elsevier, 2018)
RNAi-based gene therapy using miRNA-adapted short hairpin RNAs (shRNAmiR) is a powerful approach to modulate gene expression. However, we have observed low viral titers with shRNAmiR-containing recombinant vectors and hypothesized that this could be due to cleavage of viral genomic RNA by the endogenous microprocessor complex during virus assembly. To test this hypothesis, we targeted DROSHA, the core component of the microprocessor complex, and successfully generated monoallelic and biallelic DROSHA knockout (KO) HEK293T cells for vector production. DROSHA KO was verified by polymerase chain reaction (PCR) and western blot analysis. We produced lentiviral vectors containing Venus with or without shRNA hairpins and generated virus supernatants using DROSHA KO packaging cells. We observed an increase in the fluorescence intensity of hairpin-containing Venus transcripts in DROSHA KO producer cells consistent with reduced microprocessor cleavage of encoded mRNA transcripts, and recovery in the viral titer of hairpin-containing vectors compared with non-hairpin-containing constructs. We confirmed the absence of significant shRNAmiR processing by northern blot analysis and showed that this correlated with an increase in the amount of full-length vector genomic RNA. These findings may have important implications in future production of viral shRNAmiR-containing vectors for RNAi-based therapy. Keywords: RNAi, CRISPR/Cas9, DROSHA microprocessor, recombinant viral vector titer, producer cell line